2018
DOI: 10.1002/acn3.526
|View full text |Cite
|
Sign up to set email alerts
|

Post‐transplant adaptive function in childhood cerebral adrenoleukodystrophy

Abstract: ObjectiveHematopoietic stem cell transplantation (HSCT) is the only treatment known to slow or halt inflammatory demyelination among boys with the cerebral form of X‐linked adrenoleukodystrophy (cALD), a devastating childhood condition affecting the central nervous system. HSCT can lead to a range of adverse outcomes including fatality. Previous studies have examined the potential predictors of post‐HSCT survival and neurologic functioning. However, little is known about patients' daily‐life adaptive functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…MRI severity, the neurocognitive status of a patient at the time of HCT, treatment-related variables, and the location of the lesion may all impact the likelihood of neurological and neuropsychological morbidities in the years following treatment. 4,5,12 This retrospective study spanned over three decades with different conditioning regimens, GVH prophylaxis and potential neurotoxicity, which could have adversely affected neurocognitive function. Since moderate reduction in memory is a potential neurocognitive side effect of total body irradiation (TBI), 13,14 use of fractionated TBI conditioning could have contributed to neurocognitive deficits in two of the four patients with FWM lesions who experienced severe working memory impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI severity, the neurocognitive status of a patient at the time of HCT, treatment-related variables, and the location of the lesion may all impact the likelihood of neurological and neuropsychological morbidities in the years following treatment. 4,5,12 This retrospective study spanned over three decades with different conditioning regimens, GVH prophylaxis and potential neurotoxicity, which could have adversely affected neurocognitive function. Since moderate reduction in memory is a potential neurocognitive side effect of total body irradiation (TBI), 13,14 use of fractionated TBI conditioning could have contributed to neurocognitive deficits in two of the four patients with FWM lesions who experienced severe working memory impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together with recent studies, our findings suggest that over‐reliance on MRI severity “cutoff” scores to aid in prediction of favorable vs unfavorable outcomes may oversimplify the factors contributing to treatment response in this complex demyelinating disease. MRI severity, the neurocognitive status of a patient at the time of HCT, treatment‐related variables, and the location of the lesion may all impact the likelihood of neurological and neuropsychological morbidities in the years following treatment 4,5,12 …”
Section: Discussionmentioning
confidence: 99%
“… 4 Early intervention is critical, as long-term neurocognitive capabilities and other functional outcomes are associated with the severity of the MRI lesion and neurocognitive status at the time of HSCT. 2 , 5 7 Current understanding of outcomes is based largely on boys whose cALD was identified due to clinical signs, which may not emerge until the lesion has spread substantially. The NBS era requires that this understanding be updated.…”
mentioning
confidence: 99%
“…A total score of 0 indicates the absence of clinical signs of cerebral disease and a higher total score indicates more severe deficits. Multiple studies have shown that lower Loes and NFS scores, indicating lower stage disease, are associated with superior survival and disease control following allogeneic HCT compared to those with higher scores [16,[28][29][30].…”
Section: Allogeneic Hematopoietic Cell Transplantationmentioning
confidence: 99%